Analisis Mahasiswa dalam Memahami Kurikulum Pendidikan masa Rasulullah SAW (Studi Kasus kelas MPI dalam Mata Kuliah Pengantar Islam) - Nurrohmah, Nisa; Muqowim, Muqowim; Syasiyatun, Siti (STKIP ROKANIA, 2023)
The state of Islamic education in Indonesia actually faces a very worries fate, especially Islamic education faces various problems and gaps in more complex aspects. In the development of Islamic education, the education of the Prophet is the education adopted in the Islamic education system in Indonesia. This research uses descriptive qualitative research method with case study method. Data were collected using observation, interview, and analysis techniques. This study focuses on student analysis in understanding the educational curriculum at the time of the Prophet Muhammad, as an effort to realize effective education and achieve educational curriculum goals, and students are expected to become the relay generation of educators who are exemplified by the Prophet Muhammad.